2022
DOI: 10.31557/apjcp.2022.23.11.3869
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Acute Leukemias in Armenia: A Population-Based Study

Abstract: Objective: Leukemia represents a serious public health concern as the incidence is increasing worldwide. In this study we aimed to describe the epidemiological profile of acute lymphoblastic (ALL) and myeloid (AML) leukemia, identify disease clusters and find association with possible risk factors. Methods: Data on leukemia cases were provided by the National Institute of Health of the Republic of Armenia for the period of 2012-2018. Age-standardized incidence rate was calculated using Segi World Population. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These rates are comparable with the rates in the neighboring country Iran: 48-144 per million person-year [7] and in Europe, in average 137,5 per million person-years [8]. According to the estimates from recent population-based study conducted in Armenia, the cumulative incidence rate of the most common acute leukemias in children is about 15 to 19 per million child population [9]. However, based on data available from Pediatric Cancer and Blood Disorders Center of Armenia (PCBDCA), these estimates seriously underestimate the real rates [10].…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…These rates are comparable with the rates in the neighboring country Iran: 48-144 per million person-year [7] and in Europe, in average 137,5 per million person-years [8]. According to the estimates from recent population-based study conducted in Armenia, the cumulative incidence rate of the most common acute leukemias in children is about 15 to 19 per million child population [9]. However, based on data available from Pediatric Cancer and Blood Disorders Center of Armenia (PCBDCA), these estimates seriously underestimate the real rates [10].…”
Section: Introductionmentioning
confidence: 51%
“…The study questionnaire was developed based on instruments used in similar studies conducted in different countries [9,10], and the items were included after being adapted for the local specificities. The study instrument collected detailed information on demographic characteristics of the child and the parents, family's socioeconomic characteristics and environmental exposures, child's health and mother's pregnancy related factors with the given child.…”
Section: Study Instrument and Data Collectionmentioning
confidence: 99%
“…The major risk factors identified by scientists in a study are agricultural chemicals and electromagnetic fields and therefore in the past 10 years the cases of hematological neoplasms are constantly rising [ 9 ]. Findings on Leukaemia reported by National Institute of Health of the Republic of Armenia within the period of 2012 - 2018 indicated that there were 259 new cases of ALL and 478 AML [ 10 ]. However, the morbidity indicators obtained from the registered incidence of AML was found to be few in numbers in population based study in Kazakhstan [ 11 ].…”
Section: Introductionmentioning
confidence: 99%